Dynamical Properties of a Delay Prey-Predator Model with Disease in the Prey Species Only - Xiangyun Shi; Xueyong Zhou; Xinyu Song (Discrete Dynamics in Nature and Society)
A three-dimensional ecoepidemiological model with delay is considered. We first investigate the existence and stability of the equilibria. We then study the effect of the time delay on the stability of the positive equilibrium. The existence of a Hopf bifurcation at the positive equilibrium is obtained through the study of an exponential polynomial equation with delay-dependent coefficients. Numerical simulation with a hypothetical set of data has been carried out to support the analytical findings.